Tourism Led Growth Hypothesis: Has the Tourism industry an impact on The Economic Growth of Sao Tome and Principe? - Ribeiro, Elvira da Costa; Wang, Bing (International Journal of Economics and Financial Issues, 2019)
The importance of the tourism sector as an economic activity has increased the interest of researchers trying to understand the impact of tourism on economic growth. Therefore, the purpose of the present quantitative research is to analyze the relationship between tourism and economic growth in the case of Sao Tome and Principe employing the Tourism-led growth hypothesis (TLGH) over the period of 1997-2018, using time-series data of the following variables: Gross Domestic Product (GDP), Tourism receipts (TR), Real Exchange Rate (EX), and Foreign Direct Investment (FDI). To achieve the proposed objective, first, the unit root test was applied; the result indicated that all the 4 variables are stationary at first difference I(1), futher the Johansen for cointegration was tested and found cointegration of two-equation. The Granger causality approach was employed to enlighten the direction of causality between the variables. A unidirectional relationship was found between TR and GDP, also between FDI and all the other variables (GDP, TR, ER). Keywords: Tourism, economic growth, unit root, cointegration, causality JEL Classifications: C22, L83, O55 DOI: https://doi.org/10.32479/ijefi.9105